Metacognitive training for schizophrenia: a scoping review and phenomenological evaluation. Issue 1 (2nd January 2022) - Brar, Pavan S.; Sass, Louis; Beck, Donna; Kalarchian, Melissa A.
ABSTRACT: Background: This paper explores a possible dialogue between Metacognitive Training (MCT) for psychosis and the tradition of phenomenological psychopathol-ogy. MCT includes modules targeting cognitive and affective biases that are purported to be key mechanisms in the generation and maintenance of delusions in schizophrenia. Work in phenomenological psychopathology has also considered underlying psychological processes associated with delusions, emphasizing how distinct types of anomalous experiences may act as pathways to different types of delusions. Phenomenology's emphasis on the variety of delusional experiences suggests the importance of considering whether particular modules of MCT might be especially suited to the treatment of specific delusion types. Methods: A scoping review was used to determine whether module-specific effects on specific types of delusions occurring in SchizophreniaSpectrum Disorders (SSD) have been examined in research on MCT. Results: Results suggest that although some module-specific research exists, the heterogeneity of delusions has not been fully considered in MCT research. Discussion: We offer examples of possible ways in which particular MCT modules may be differentially effective, and we advocate placing greater focus on the phenomenology and measurement of different types of delusions in future research.